Pusat Komik dan Animasi di Kota Banda Aceh dengan Pendekatan Modern Berkelanjutan - Hanindhifa Azzahra; Zulfikar Taqiuddin; Muliadi Muliadi (Jurnal Serambi Engineering, 2022)
Comics and Animation is currently one of the media that can raise various themes, ranging from entertainment, education, business, and politics. However, the facilities in Banda Aceh are considered inadequate for this comic and animation activity. In addition, the place to hold comic and animation exhibitions is also not available, this is feared considering that the field of comics and animation requires adequate facilities and proper management. Therefore, this writing aims to create or design a center of comic and animation activities that can be a place or container for the people of Aceh. This Comic and Animation Center will be located in Tentara Siswa Street, Kampung Baru, Baiturrahman District, Banda Aceh City. This design takes the theme of Modern Contemporary and Sustainable Architecture. The use of this theme of Modern Contemporary and Sustainable Architecture recalls the present that not onlyattaches importance to the architectural style of the present but also the sustainability of the building in the future by reducing the negative environmental impact.